Work-based higher education programmes in Germany and the US: Comparing multi-actor corporatist governance in higher education. Issue 1 (2nd January 2017) - Graf, Lukas
Abstract: In both Germany and the United States, employers search for new strategies to recruit and train people in times of a dynamically evolving economy and rising educational expectations on the part of individuals. In this context, we observe the proliferation of work-based higher education programmes in both countries. This development challenges the common classification found in the political economy and educational policy literature that distinguishes between collectively governed dual apprenticeships in Germany and market-driven on-the-job training in the US. The paper proposes an alternative conceptualization that identifies significant similarities in the governance mode of work-based higher education across the two countries. Based on expert interviews and document analysis, the institutional analysis focuses on complex multi-actor governance constellations at the nexus of vocational training and higher education and explores consequences for contemporary policy-making in advanced skill formation.